Pancasila Sebagai Landasan Perlindungan HAM dalam Konflik Investasi Pariwisata Raja Ampat - Nadia Imtinan Arka Salmah (Badan Pembinaan Ideologi Pancasila, 2025)
The conflict between tourism investment and the protection of human rights (HR) in the conservation area of Raja Ampat reflects the tension between economic development and socio-ecological sustainability. Although the tourism sector is often regarded as a more sustainable development alternative, investment practices in this region have led to human rights violations, such as the appropriation of customary land, the exclusion of indigenous communities from decision-making processes, and environmental degradation that directly affects local cultural and social life. This study aims to analyze how Pancasila can serve as a normative foundation for ensuring human rights protection amid tourism investment conflicts in Raja Ampat. This research employs a normative juridical approach, with data obtained from literature reviews, legal documents, institutional reports, and recent media coverage. The analysis is conducted qualitatively using a legal hermeneutic approach that focuses on the values of Pancasila as an evaluative framework. The findings show that the principles of Pancasila, particularly the second and fifth principles provide a strong ethical and constitutional basis for safeguarding the rights of indigenous communities, including their rights to a healthy environment, land ownership, and self-determination. Applying Pancasila in policy formulation related to tourism investment and management offers a potential alternative solution to development-related conflicts, while reinforcing social and ecological justice in strategic national areas such as Raja Ampat.